Beliefs and experiences in the English classroom: Perspectives of Swedish primary school learners - Nilsson, Maria (Studies in Second Language Learning and Teaching, 2020)
This study investigates how Swedish learners make sense of and perceive English instruction and the process of foreign language learning in a target language-only primary school classroom. In small group discussions, 26 learners aged 9-10 were audio recorded while discussing questions related to their language learner beliefs and their classroom experiences. Learners expressed a strong consensus about the importance of both the teacher’s extensive target language input and the learners’ oral engagement, in alignment with the beliefs of the teacher. However, the analysis identified three mismatches among high anxiety learners in this context, related to incomprehensible teacher talk, social fear of making mistakes and classroom organization. As their voiced beliefs were at odds with their emotionally guided behavior of refraining from asking questions or volunteering to speak, their sense of agency was reduced. In this context, the target language-only approach appeared to have a negative impact on the emotional, organizational and instructional dimensions of foreign language instruction for many of the young learners. The findings illustrate the interrelated dynamics of beliefs, emotions and classroom context, and contribute to our understanding of learners’ foreign language anxiety and sense of agency in the primary foreign language classroom.